Defisit Kepastian Autentikasi Alat Bukti Elektronik dalam Penyidikan Delik Digital Pasca-Harmonisasi UU ITE dan KUHAP 2025 - Reggy Indra Pratama; Ujuh Juhana (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
Digital transformation has shifted conventional crime into data-driven offenses, where electronic evidence is latent, fragile, and vulnerable to manipulation. Indonesia's Law Number 1 of 2024 on Electronic Information and Transactions (ITE Law) and Law Number 20 of 2025 on the Criminal Procedure Code both recognize electronic evidence, yet they originate from different legal regimes, creating challenges in normative harmonization during digital-crime investigations. This study examines the harmonization of electronic evidence between the ITE Law and the 2025 Criminal Procedure Code and evaluates its implications for legal certainty. This normative (doctrinal) legal research employs descriptive-analytical methods through statutory, conceptual, and comparative approaches. Primary legal materials include the ITE Law and the 2025 Criminal Procedure Code, while secondary and tertiary materials consist of accredited legal scholarship, ISO/IEC 27037, and library sources analyzed qualitatively using deductive reasoning. The findings demonstrate that the two laws complement one another in recognizing electronic evidence, with the ITE Law extending evidentiary categories and the 2025 Code establishing electronic evidence as independent evidence requiring authentication. However, legal certainty remains limited because digital forensic procedures remain discretionary and no mandatory chain-of-custody standard exists, creating authentication asymmetry, particularly regarding AI-generated synthetic evidence. The study proposes operational harmonization through technical investigative guidelines, mandatory digital chain-of-custody standards, forensic certification, and mechanisms for verifying synthetic evidence to strengthen legal certainty and safeguard suspects' rights.